Evidence for the presence of a vasoactive substance (possibly involved in the aetiology of cerebral arterial spasm) in cerebrospinal fluid from patients with subarachnoid haemorrhage. - Boullin, D J (1976)
Cerebrospinal fluid from patients with subarachnoid haemorrhage and cerebral arterial spasm contracted the isolated basilar artery and potentiated contractions produced by 5-hydroxytryptamine, noradrenaline, and six prostaglandins. The unidentified substance in cerebrospinal fluid probably plays a role in the aetiology of cerebral arterial spasm.